PEMBENTUKAN SEKOLAH PEREMPUAN: EDUKASI KESEHATAN REPRODUKSI DAN PENINGKATAN STATUS GIZI PADA PEREMPUAN DI DESA PUDAK KABUPATEN MUARO JAMBI: Sekolah Perempuan - Kalsum, Ummi; Guspianto, Guspianto; Asparian, Asparian; Muldiasman, Muldiasman; Sitanggang, Hendra Dhermawan; Octaviana, Tarra; 'Aisya, Nakhlatul (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2026)
Women's health issues remain an important issue in Indonesia, especially those related to reproductive health and poor nutritional status among women of productive age. Lack of knowledge makes them vulnerable to nutritional problems such as anemia, chronic energy deficiency (CED), pregnancy complications, and reproductive health disorders that lead to domestic violence. This community service program aims to increase women's knowledge and awareness to improve their health independence through the establishment of a Women's School in Pudak Village, Muaro Jambi Regency. The activity was carried out using a community-based participatory approach, which involved women, village officials, and health workers in every stage of implementation. The stages of the activity included advocacy, socialization, the establishment of the Women's School, the implementation of reproductive health and nutrition education, and evaluation through pre-tests and post-tests. This activity successfully fostered awareness, enthusiasm, and commitment among participants to apply reproductive health and balanced nutrition practices in their daily lives and prevent domestic violence. The formation of Women's School cadres is an important achievement for the sustainability of education and women's empowerment at the village level.